Edukasi Lingkungan Ramah Anak Mendorong Penggunaan Tumbler untuk Mengurangi Sampah Botol Minum di Sekolah Dasar - Nadya Dominica Putri Yudda; Komang Widhya Sedana Putra P; Nyoman Sri Manik Parasari; Sahri Aflah Ramadiansyah (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Environmental problems caused by plastic waste, especially from disposable drinking bottles, are increasing in Indonesia. One solution to reduce plastic waste in elementary schools is through child-friendly environmental education that encourages the use of tumblers. Objective: This study aims to educate students about the benefits of protecting the environment by reducing the use of disposable plastic bottles. Method: The method used in this study consists of three main stages, namely counseling, practice, and monitoring and evaluation. Counseling is carried out through educational sessions involving students, teachers, and parents. The practice stage involves a campaign to use tumblers and distribute tumblers to students. Monitoring and evaluation are carried out to measure changes in student habits in using tumblers. Result: The results of the study imply an increase in students' interpretation of the negative impacts of plastic waste from 40% to 85%. The habit of bringing tumblers increased from 30% to 70%, and 65% of students began to consistently use tumblers at school. Conclusion: This program is effective in building environmental awareness and responsibility among students. Recommendations for program sustainability include strengthening school policies and integrating environmental education into the curriculum.